Joe Pickett : Wolf Pack - Book 19 - Box, C. J. (New York : G.P. Putnam'S Sons, 2019)
Wyoming game warden Joe Pickett encounters bad behavior on his own turf--only to have the FBI and the DOJ ask him to stand down--in the thrilling new novel from #1 New York Times-bestselling author C.J. Box.
Publishers Weekly
Booklist
Kirkus Reviews
Library Journal Prepub Alert
Adult
Keywords: Murder -- Fiction -- Investigation; Conspiracies -- Fiction; Suspense fiction